WAWANCARA KLINIS DALAM BAHASA IBU UNTUK MEREMEDIASI MISKONSEPSI SISWA PADA MATERI CAHAYA DI SD - Febriana, Febriana; Tiur, Haratua; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to decrease elementary school student?s misconception about light using clinical interview in mother tongue. Purposive sampling was used in this research that involvied 22 students as sample. They are respectively divided into three level of knowledge such as high, middle, and low knowledge category based on teacher recommendations referring to study achievement of students. The instrument that used is multiple choice with three alternative option, and clinical interview guidelines.  Based on McNemar test showed that there significant misconception change with  >  with df=1 and ?= 5%.  Clinical interview in mother tongue can used as alternative to decrease student?s misconception about light. Keywords: clinical interview, decreasing misconception, light.